2014
DOI: 10.1007/s00449-014-1213-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visible light on catalytic hydrolysis of p-nitrophenyl palmitate by the Pseudomonas cepacia lipase immobilized on sol–gel support

Abstract: This paper demonstrates Pseudomonas cepacia lipase catalyzed hydrolysis of p-nitrophenyl palmitate under irradiation of light with wavelengths of 250-750 nm. The reaction follows Michaelis-Menten Kinetics and the light irradiation increases the overall rate of hydrolysis. Using Lineweaver-Burk plot K M and V max values for the reaction in presence of light are found to be 39.07 and 66.67 mM/min/g, respectively; while for the same reaction under dark condition, the values are 7.08 and 10.21 mM/min/g. The linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It was also revealed that LPC had the highest catalytic activity in this assay with a distinct hyperbolic curve compared to the other esterases and LPL, releasing 8 nmols 4-nitrophenol in 30 min (Figure 2C,D). Ganasen et al studied the hydrolysis of 4-nitrophenyl palmitate with LPC on an immobilized support, at various substrate concentrations, and determined the hyperbolic curves of activity for all substrate concentrations, which are similar to our findings (Figure 2B) [30].…”
Section: Hydrolysis Of 4-nitrophenyl Palmitate Mediated By Esterases ...supporting
confidence: 88%
“…It was also revealed that LPC had the highest catalytic activity in this assay with a distinct hyperbolic curve compared to the other esterases and LPL, releasing 8 nmols 4-nitrophenol in 30 min (Figure 2C,D). Ganasen et al studied the hydrolysis of 4-nitrophenyl palmitate with LPC on an immobilized support, at various substrate concentrations, and determined the hyperbolic curves of activity for all substrate concentrations, which are similar to our findings (Figure 2B) [30].…”
Section: Hydrolysis Of 4-nitrophenyl Palmitate Mediated By Esterases ...supporting
confidence: 88%
“…The study showed an enhancement in the enzyme activity due to the conformational changes that occurred in the α‐amylase when the protein was illuminated with visible polarized and non‐polarized light. Moreover, in our recent study, we reported that Pseudomonas cepacia lipase can accelerate the rate of hydrolysis of p‐ nitrophenyl palmitate in the presence of visible light irradiation . However, as far as the authors are concerned, no one has reported the lipase catalyzed esterification reactions under the influence of light.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our recent study, we reported that Pseudomonas cepacia lipase can accelerate the rate of hydrolysis of p-nitrophenyl palmitate in the presence of visible light irradiation. [15] However, as far as the authors are concerned, no one has reported the lipase catalyzed esterification reactions under the influence of light. Therefore, the purpose of our current study is to explore the effect of light on the esterification reactions MONTH 2019 THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING 1 catalyzed by Pseudomonas cepacia lipase.…”
Section: Introductionmentioning
confidence: 99%